Are pulmonary neuroepithelial bodies sensors for acute airway hypoxia implicated in the central regulation of breathing? - Inge Brouns; Kathy Schnorbusch; Isabel Pintelon; Robrecht Lembrechts; Ian De Proost; Paul J. Kemp; Jean-Pierre Timmermans; Dirk Adriaensen (PLoS ONE, 2026)
Although their functions have long been disputed, pulmonary neuroepithelial bodies (NEBs) are now considered complex, multifunctional units implicated in vagal sensory signaling within the brain–lung axis. A widely proposed function of NEBs is that their neuroendocrine cells would be able to sense acute airway hypoxia, triggering Ca² ⁺ -dependent transmitter release and the subsequent activation of vagal afferents that transfer the hypoxic information to the central nervous system (CNS). However, physiological evidence for the latter well-documented hypothesis is so far inconclusive. Using a confocal live-cell imaging model, based on murine precision-cut lung slices (PCLSs), this study was designed to directly visualize hypoxia-induced activation of NEB cells, including associated Ca² ⁺ -mediated exocytotic events that would support CNS-directed signaling. In PCLSs from prenatal and postnatal C57BL/6 mice, including GAD67-GFP mice, we monitored changes in intracellular Ca²⁺ ([Ca²⁺] i ), mitochondrial membrane potential, and reactive oxygen species (ROS) during acute and intermittent hypoxia, as well as after ROS scavenging. Whole-mount mouse carotid bodies served as positive controls. Carotid body glomus cells showed robust hypoxia-induced [Ca²⁺] i rises, confirming assay sensitivity. In contrast, neither acute (2 or 12% O₂) nor intermittent hypoxia elicited [Ca²⁺] i increases in NEBs or delayed activation of adjacent Clara-like cells at any developmental stage. NEBs remained responsive to K + -induced depolarization, though excitability appeared to decrease during hypoxia. Hypoxia caused rapid, reversible mitochondrial depolarization in NEBs and ciliated epithelial cells, accompanied by a modest ROS increase in all airway epithelial cells. Tempol did not uncover any [Ca²⁺] i responses. Whereas control airway epithelium and carotid body expressed all NADPH oxidase subunits, the NEB microenvironment appeared to lack clear expression of several components. We conclude that mouse NEBs do not exhibit Ca² ⁺ -mediated exocytotic responses to hypoxia and that NADPH oxidase is unlikely to function as their O₂ sensor. These findings challenge a direct NEB-to-brain signaling pathway for acute hypoxia, but support local, paracrine functions related to airway oxygenation.